The Patterns of Adjective Phrase in Bahasa Mentawai: An Analysis of X-Bar - Rahmawati, Kartika Eva; Subiyanto, Agus (Syntax Literate, 2021)
In order to figure the structure of adjective phrase, X-Bar theory is used to present the detailed formulation. Therefore, this theory is applied in this study to investigate the patterns of the formation of adjective phrases in Bahasa Mentawai and the kind of adjective categories (attributive or predicative) that appear based on the patterns. Then, this study also has a purpose to present the forms of the adjective phrase in Bahasa Mentawai using the X-Bar theory. The data is taken from a book that contains many sentences in Bahasa Mentawai. Then, the descriptive-qualitative method was chosen to present the analysis in detail. The results present the patterns in X-Bar pattern to make Adj and PP is FA (AF) à A’ à A’ + FP (PF), to make Adj and NP is FAà A’ à A + FN (NP), to make Adj and AP is FA à A’ à A’ + A, and to make Adj and Adv P is FA à A’ à Adv’ + A. Last, the type of adjective categories that occur in Bahasa Mentawai is predicative where the adjective has a function to explain something before it appears.